Autonomous driving cargo bikes – Introducing an acceptability-focused approach towards a new mobility offer - Karen Krause; Tom Assmann; Stephan Schmidt; Ellen Matthies (Transportation Research Interdisciplinary Perspectives, 2020)
Autonomous Driving as a possible, almost likely future of mobility offers new scenarios to move. In the present study, we take the first step to transfer the vision of mobility as a service on autonomous driving cargo bikes: users will be able to call a cargo bike, use it for multiple purposes and release it again for others to use. To ensure broad applicability in different mobility scenarios as well as addressing individual mobility needs while offering intuitive operability, we followed an interdisciplinary approach. While the challenge to realize this vision on a technical level was prepared, both logistics and human sciences collaborated in developing data collection instruments and using user-centered development methods. In detail, we used online questionnaires to describe mobility needs on the test field of a university's' campus. Secondly, we used focus groups to discuss points relevant to future users' needs for the autonomous driving cargo bike as well as discussion points with other road users who would encounter the cargo bike in traffic. We integrated results from those different approaches to formulate construction indications and points for future research.